Engagements with narrative - Utell, Janine, 1975- (London ; New York : Routledge, 2016)
"Balancing key foundational topics with new developments and trends, Engagements with Narrative offers an accessible introduction to narratology. As new narrative forms and media emerge, the study of narrative and the ways people communicate through imagination, empathy, and storytelling is especially relevant for students of literature today. Janine Utell presents the foundational texts, key concepts, and big ideas that form narrative theory and practical criticism, engaging readers in the study of stories by telling the story of a field and its development. Distinct features designed to initiate dialogue and debate include: - Coverage of philosophical and historical contexts surrounding the study of narrative - An introduction to essential thinkers along with the tools to both use and interrogate their work - A survey of the most up-to-date currents, including mind theory and postmodern ethics, to stimulate conversations about how we read fiction, life writing, film, and digital media from a variety of perspectives. - A selection of narrative texts, chosen to demonstrate critical practice and spark further reading and research - "Engagement" sections to encourage students to engage with narrative theory and practice through interviews with scholars This guide teaches the key concepts of narrative--time, space, character, perspective, setting--while facilitating conversations among different approaches and media, and opening paths to new inquiry. Engagements with Narrative is ideal for readers needing an introduction to the field, as well as for those seeking insight into both its historical developments and new directions"--
Includes bibliographical references and index.
Keywords: Narration (Rhetoric); LITERARY CRITICISM / General